Русская история в жизнеописаниях ее главнейших деятелей - Костомаров Николай Иванович (1991)
Экземпляры: ЧЗ (20151030) / Инвентарный номер: 30022 / Цена: 18 / Авт.знак: К 72 / ГРНТИ: 03 / ББК: 63.3(2)45